Phosphate Diester Cleavage Promoted by the Metallomicelles of Ce(III) Complexes of Aza-Crown Ether with Different Numbers of Nitrogen Atoms. Issue 3 (3rd March 2016) - Feng, Fa-Mei; Cai, Shu-Lan; Liu, Fu-An
Abstract : The design of artificial hydrolase has attracted extensive attention due to their scientific significance and potential application in the field of gene medicine and molecular biology. This work reports the catalytic activation of two aza-crown ether Ce(III) complexes and their metallomicelles as artificial hydrolase in bis(4-nitrophenyl) phosphate ester (BNPP) hydrolysis. The chemical composition of two complexes was determined by the fluorescence spectra and the mole ratio method for electronic absorption spectra. The bonding effect of BNPP and solubilizing effect of the complexes were proved by a method of fluorescence spectroscopy. The catalytic activity of different catalytic systems in BNPP hydrolysis was measured with UV-vis spectrophotometric method. These catalytic systems showed high catalytic activity for promoting BNPP hydrolysis at the almost physiological conditions. BNPP hydrolysis rate in these catalytic system is about 10 7 - to 10 9 -fold faster than that of the BNPP spontaneous hydrolysis in aqueous solution at the same conditions. The metallomicelle systems exhibited higher catalytic activity compared with the complex solution systems in BNPP hydrolysis, and hexadecyltrimethyl ammonium bromide micelle provides a useful catalytic environment for reaction. The acid effect of the catalytic system is ascribed to the formation of metal-bound hydroxide serving as a better kind of nucleophile. GRAPHICAL ABSTRACT: